Haze effects on the propagation of free space optical communications in Malaysia - Sheikh Naimullah, Bibi Sarpinah; Hitam, Salasiah; Hazwan, W. M.; Othman, Maisara; Abdullah, Mohamad Khazani (Federation of Engineering Institutions of Islamic Countries, 2006)
This paper presents the effect of atmospheric attenuation during hazy days for free space optical (FSO) communication in point-to-point connection. The analysis focuses on scattering coefficient and atmospheric attenuation effects on low visibility, which falls in the range of 1.8 km to 4.5 km. The performance comparison is also done for the wavelength of 850 nm and 1550 nm. The result shows that the performance of 1550 nm is better than 850 nm in both performance parameters. As the link range between transmitter and receiver increases, the atmospheric attenuation increases too. Using small divergence, small transmitter aperture, and large receiver aperture and deployment distance of less than 1km can reduce the effect of atmospheric attenuation. These challenges limit FSO to the short distance application.